2018
DOI: 10.7554/elife.39611
|View full text |Cite
|
Sign up to set email alerts
|

Multiple serine transposase dimers assemble the transposon-end synaptic complex during IS607-family transposition

Abstract: IS607-family transposons are unusual because they do not have terminal inverted repeats or generate target site duplications. They encode two protein-coding genes, but only tnpA is required for transposition. Our X-ray structures confirm that TnpA is a member of the serine recombinase (SR) family, but the chemically-inactive quaternary structure of the dimer, along with the N-terminal location of the DNA binding domain, are different from other SRs. TnpA dimers from IS1535 cooperatively associate with multiple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 64 publications
0
15
0
Order By: Relevance
“…In short, tnpA-07 plays a key role in the co-occurrence network of macrolides and chloramphenicol resistance genes, and the connection point of the two large modules is tnpA-03. Previous studies have shown that MGEs, as the main promotion unit of horizontal transfer, play an important role in the occurrence and spread of ARGs (Chen et al, 2018, Zheng et al, 2018. In summary, the occurrence and spread of ARGs in sediments is highly correlated with MGEs, especially the tnpA gene plays a key role in the co-occurrence of ARGs.…”
Section: Analysis Of Args In Uencing Factorsmentioning
confidence: 77%
See 1 more Smart Citation
“…In short, tnpA-07 plays a key role in the co-occurrence network of macrolides and chloramphenicol resistance genes, and the connection point of the two large modules is tnpA-03. Previous studies have shown that MGEs, as the main promotion unit of horizontal transfer, play an important role in the occurrence and spread of ARGs (Chen et al, 2018, Zheng et al, 2018. In summary, the occurrence and spread of ARGs in sediments is highly correlated with MGEs, especially the tnpA gene plays a key role in the co-occurrence of ARGs.…”
Section: Analysis Of Args In Uencing Factorsmentioning
confidence: 77%
“…SmartChip qPCR software was used to analyze the results, multiple peaks or wells whose ampli cation e ciency exceeded the range (90%-110%) were excluded and then screened for (1) A threshold cycle (CT) must be ≤31, (2) Positive samples must be repeated three times simultaneously. Calculate the relative copy number (Eq.1) was calculated based on previous studies (Chen et al, 2018). In addition, the method of comparing CT was also used to calculate the FC value of ARGs between the modi ed sample and the control (Eq.…”
Section: Dna Extraction and High-throughput Quantitative Pcrmentioning
confidence: 99%
“… C) OPG61 (F16L) (blue, aa 1-118 (of 231)) and best cellular Dali hit, the catalytic domain of a serin recombinase from Sulfolobus sp. L00 11 (archaea) (pdb 6dgc, (61) green, aa 65-164 (of 211)). Exemplified catalytic subdomain DRLXR (aa 139-143) in serin recombinase (magenta) and mutated stretch KQISI (aa 73-77) in OPG61 (cyan) are highlighted.…”
Section: Resultsmentioning
confidence: 99%
“… D) Structural alignment of prototype OPG61 (Q), 7 OPG members from diverse chordopoxviruses (blue, from top to bottom:MPXV Zaire 96-I-16, VACV, VARV, MCV subtype 1, SFV, MyxV and SORPV)) and three Dali hits (green, an integrase from Lactococcus phage TP901-1 (3bvp-B (62)), an IS607-like serine recombinase from Sulfolobus sp. L00 11 (6dgc-D (61)) and a resolvase family site-specific recombinase from Streptococcus pneumoniae SP19-BS75 (3guv-A (63)). Red bar highlights catalytic center (DRLxR motif) of serin recombinases.…”
Section: Resultsmentioning
confidence: 99%
“…12 OptrA is often located on chromosomes or plasmids and can be transmitted by mobile genetic elements such as transposons and insertion sequences. [13][14][15] The most recently reported poxtA gene, mediating resistance to oxazolidinones, tetracyclines, and phenicols, was first described in an MRSA isolate from respiratory secretion of an Italian patient. 8 Since its first report, it has also been detected in isolates from animals and humans in many countries, including Italy, Greece, and China.…”
Section: Introductionmentioning
confidence: 99%